(3JfRjd GdScjfI Ydi bfGOjd GdeOjfIs - (3Ydj Hf YHO GdcGaj Hf Ydj Hf JeGe GdSHcj GdCfUGQj GdNRQLj, CHh GdMSf, Jbqj GdOjf,J (B756 (3g` s ((3YHO GdQMef GdCTehfi s)
(3ChdgG (B:s
(3hHYO aEf Gddg jYde Cf cd NjQ CfG ajg hef Ydi Hg agh SHH GdfHi Udi Gddg Ydjg hSde hEdJLGFi Edjg HGH cShI GdcYHI s
(3BNQgG (B:s
(3hGdeSGLO GdKdGKI HYOe TgGOI GdTQY dgG hCf ef NQL ef eGdg Yf TF dgG hGbJVi GdYQa UQag ai LgI ef LgGJgG UQa hGNJUJ Hg hGddg GYde gPG BNQ GdcJGH s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B302s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B494s
(3eUOQ GbJfGA GdCUd (B:s
(3GdeQJH GdGLOi (B/ (3YehejI (B(1905) s
Keywords: (3GdMOjK h GdeUWdMs